Energy expenditure in novice skiers and snowboarders - Aerenhouts, D.; De Raedermaeker, L.; Clarys, P.; Zinzen, E. (Science and Skiing VI. 6th International Congress on Science and Skiing, Dec. 14 - 19, 2013, St. Christoph am Arlberg, 2015)
The aim of the present study was to estimate energy expenditure and intensity in novice skiers and snowboarders. Secondly, this study investigated if an evolution in energy expenditure can be observed during the first days of learning how to ski or snowboard.